Advance Care Planning in Nursing Homes – Improving the Communication Among Patient, Family, and Staff: Results From a Cluster Randomized Controlled Trial (COSMOS) - Aasmul, Irene; Husebo, Bettina S.; Sampson, Elizabeth L.; Flo, Elisabeth (Frontiers in Psychology, 2018)
Introduction: The majority of nursing home patients suffer from complex diseases, including dementia. This makes advance care planning particularly important. Objectives: The aim was to investigate the effect of an advance care planning intervention on communication between nursing home staff, the patient and family. We further investigated whether the intervention affected nursing staff distress. Methods: The advance care planning intervention was a part of the 4-month cluster randomized controlled COSMOS trial with a 9-month follow-up. Norwegian nursing home units (n = 72), with 765 patients were invited, and eligible units were cluster randomized to usual care or the intervention group. The advance care planning intervention consisted of an education program targeting all NH staff (nurses and physicians) and managers. Implementation was supported by a train-the trainer approach, with regular phone calls from the researchers. The effect of the intervention was assessed by a data collection form and questionnaires. Nursing staff distress was assessed by the Neuropsychiatric Inventory -Nursing Home version. Results: There were 297 patients in the intervention group (36 NH-units) and 248 patients in the control group (31 NH-units) participating. Organized meetings between the family, patient and nurses were conducted significantly more frequently in the intervention group compared to the control group at month 4 (OR = 3.9, 95% CI = 1.6 to 9.4, p = 0.002). Monthly contact between family and nurses was also more frequent in the intervention group (OR = 6.5 95% CI 1.6 to 3.5, p = 0.010). Nurses and families were more satisfied with their communication in the intervention group compared to the control group. Nursing staff distress was reduced in the intervention compared to control group at month 4 (B = -1.8, 95% CI = -3.1 to -0.4, p = 0.012). The intervention effect at month 4 did not persist on follow-up at month 9. Conclusion: The study improved the frequency of, and satisfaction with communication. Furthermore, nursing staff distress was reduced in the intervention group. The follow-up assessment indicates the need for ongoing staff support and guidance. Trial registration: clinicaltrials.gov (NCT02238652).